Rancang Bangun Sistem Informasi Sekolah di SMK Negeri 1 Jetis Mojokerto - Yunanto, Andhik Ampuh; Martono, Hero Yudo; Prasetyaningrum, Ira; Ahsan, Ahmad Syauqi; ., Nailussa’ada; Asmara, Rengga; Wibowo, Prasetyo; Santoso, Dian Septiani; Humaira, Fitrah Maharani; Al, Mohammad Jawahir; Panggalih, Bintang Ampuh; Hidayatullah, Taufiq; Zufar, Farhan Izzudin Az; Hasnaa, Rosyiidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The school information system, especially the Industrial Work Practices activity attendance system at SMKN 1 Jetis, is still done manually, that is, it still uses books and you have to fill in an activity journal every day in that book. After the internship ends, students are asked to collect the books, which the teacher will use to collect data on whether the student skipped class, permission and so on. Meanwhile, teachers do not have other data that can be used for data collection if the book is damaged or lost. This problem occurs because there is no system or application that is able to provide convenience for the process of collecting data and checking accurately. This information system created uses web or mobile technology which is tailored to the needs of system users and can make it easier for teachers to carry out the process of checking student attendance at internship activities through this attendance application, and we also provide a comparison of this application with other applications in order to determine the quality application quality and to determine the development of application features aimed at making it easier for users to use the application.